2022
DOI: 10.21203/rs.3.rs-1190081/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposure Characteristics of Phthalate Metabolites Among The Zunyi Cohort of Pregnant Women in Southwest China

Abstract: Reported evidence has increasingly indicated that exposure to phthalates can cause adverse pregnancy outcomes. However, phthalate exposure levels among pregnant women remains unclear. We aimed to evaluate the concentrations of phthalate metabolites in urine samples of the Zunyi cohort of pregnant women from Southwest China. The study was conducted between August 2020 and July 2021, and urine samples were collected from 1003 pregnant women during their third trimester of pregnancy. The concentrations of nine ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Then, we analyzed the RNA-seq data of bcf-1 mutant (He et al, 2023) and found that up-regulated genes involved in neuropeptide signaling pathway are enriched (Figure S4A) and neuropeptide genes are up-regulated in bcf-1 mutant (Figure S4B). Neuropeptides are reported as signal to regulate cell nonautonomous UPR mt (Berendzen et al, 2016;Chen et al, 2021;Liu et al, 2022), especially from neuron to intestine. Thus, we asked whether intestinal expressed bcf-1 regulates UPR mt through neuronal signals.…”
Section: Bcf-1 Mutation Activates Upr Mt Through Cell-non-autonomous ...mentioning
confidence: 99%
“…Then, we analyzed the RNA-seq data of bcf-1 mutant (He et al, 2023) and found that up-regulated genes involved in neuropeptide signaling pathway are enriched (Figure S4A) and neuropeptide genes are up-regulated in bcf-1 mutant (Figure S4B). Neuropeptides are reported as signal to regulate cell nonautonomous UPR mt (Berendzen et al, 2016;Chen et al, 2021;Liu et al, 2022), especially from neuron to intestine. Thus, we asked whether intestinal expressed bcf-1 regulates UPR mt through neuronal signals.…”
Section: Bcf-1 Mutation Activates Upr Mt Through Cell-non-autonomous ...mentioning
confidence: 99%